2024
DOI: 10.1186/s12885-023-11786-2
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing serum metabolomics for assessing postoperative efficacy and monitoring recurrence in gastric cancer patients

Tong Qu,
Shaopeng Zhang,
Shaokang Yang
et al.

Abstract: Objective (1) This study aims to identify distinct serum metabolites in gastric cancer patients compared to healthy individuals, providing valuable insights into postoperative efficacy evaluation and monitoring of gastric cancer recurrence; (2) Methods: Serum samples were collected from 15 healthy individuals, 16 gastric cancer patients before surgery, 3 months after surgery, 6 months after surgery, and 15 gastric cancer recurrence patients. T-test and analysis of variance (ANOVA) were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nucleotide metabolism is considered to be the most critical link between tumorigenesis and tumor cell replication. Studies have shown that the polymerase activity of DNA and RNA synthesis in tumor tissues is greater than that in normal tissue, nucleotide synthesis is increased, and decomposition is reduced[ 30 - 32 ]. As a result, nucleotide metabolites are upregulated in the cancer state to meet the uncontrolled and rapid self-growth needs of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide metabolism is considered to be the most critical link between tumorigenesis and tumor cell replication. Studies have shown that the polymerase activity of DNA and RNA synthesis in tumor tissues is greater than that in normal tissue, nucleotide synthesis is increased, and decomposition is reduced[ 30 - 32 ]. As a result, nucleotide metabolites are upregulated in the cancer state to meet the uncontrolled and rapid self-growth needs of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism deregulation is one of the most familiar metabolic alterations in cancer [ 60 ]. Interestingly, a study examining differential serum metabolites showed significant alterations in the abundance of several metabolites among patients before and after surgery [ 61 ]. Particularly, lysophosphatidic acids, triglycerides, lysine, and sphingosine-1-phosphate revealed increased levels in the postoperative groups compared with the preoperative and recurrence groups.…”
Section: Metabolomics-based Validation Of Predictive and Prognostic M...mentioning
confidence: 99%